Restorative Justice Principles in Banjar Customary Inheritance Disputes: A Normative Analysis of Out-of-Court Settlement Institutions through Adat Badamai - Akhmad Sukris Sarmadi; Anwar Hafidzi; Nurul Listiyani; Tetiana Kolomoiets; Afif Khalid (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
Inheritance disputes in Banjar communities continue to increase as families confront controversies over unwritten norms, generational change, and rising land value, creating a growing need for culturally grounded solutions. These disputes reflect a broader trend in Indonesia where communities prefer non-court settlement when judicial rulings risk disrupting social cohesion. Within this plural legal landscape, families must navigate overlapping expectations from customary norms, Islamic law, and state regulations. This study addressed a key gap by examining how restorative justice principles operate within Banjar inheritance practices. Using a qualitative normative method, the research analyzed primary legal materials, documented customary procedures, court decisions, and academic literature. The findings showed that adat badamai integrated restorative values through open dialogue, inclusive deliberation, and relational repair among heirs. The study concluded that adat badamai provides an effective culturally rooted model of restorative justice and recommends stronger legal recognition and enhanced mediator training.